Shore to Store: An Export Readiness Strategy for Coastal MSMEs in Sanur through Digital Literacy Mediated by Strategic Agility - Ketut Vini Elfarosa; Luh Kemala Putri Widhiari; Eldian Rinaldi; Leni Anggraini Susanti; Ni Putu Ritra Trees Ari Kartika Hadi Saraswati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2026)
The low participation of Micro, Small, and Medium Enterprises (MSMEs) in export activities remains a major challenge in developing sustainable coastal economies. This study examines the effect of digital marketing literacy on export readiness among shell-craft MSMEs in the coastal area of Sanur, Bali, with strategic agility as a mediating variable, and identifies improvement priorities using Importance-Performance Map Analysis (IPMA). A quantitative approach was employed through a survey of 62 shell-craft MSMEs selected using accidental sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and IPMA. The results reveal that digital marketing literacy significantly influences strategic agility (β = 0.616; p less than 0.001) and export readiness (β = 0.293; p = 0.016). Strategic agility positively affects export readiness (β = 0.500; p less than 0.001) and partially mediates the relationship between digital marketing literacy and export readiness (β = 0.308; p less than 0.001). IPMA findings indicate that social media promotion, digital payment use, digital catalog management, customer data analysis, and market-driven product innovation are high-importance but low-performance attributes. This study proposes the “Shore to Store” model as a strategic framework to accelerate the transformation of coastal MSMEs into export-ready enterprises.